Comprehensive cytokine profiling provides evidence for a multi-lineage Th responses in Guillain Barré Syndrome. (October 2018) - Debnath, Monojit; Nagappa, Madhu; Talukdar, Pinku Mani; Subbanna, Manjula; Sundaravadivel, P.; Shivakumar, Venkataram; Dutta, Debprasad; Wahatule, Rahul; Sinha, Sanjib; Bindu, Parayil Sankaran; Periyavan, Sundar; Umamaheswara Rao, G.S.; et al.
Highlights: Cytokines mediate the progression and recovery of GBS. Cytokines belonging to Th1, Th2 and Th17 pathways are associated with GBS. Cytokines also influence symptom duration in GBS. Abstract: Guillain Barré Syndrome (GBS) is one of the commonest acquired immune-mediated neuropathies, often preceded by infections. Although cellular immune responses are shown to substantially account for the pathophysiology of GBS, the precise mechanistic basis of risk and disease course remains enigmatic till date. Cytokines are best known for their abilities to drive cellular immunity and inflammation through their co-ordinated actions. Data obtained from clinical and animal model studies suggest important implications of some of the cytokines in the progression and recovery of GBS. However, these studies were performed on few cytokines and small set of GBS patients, thereby lacking a complete understanding of the patterns of association of cytokines representing Th1, Th2, and Th17 responses with GBS. We studied 65 well-characterized GBS patients and 73 age- and sex-matched healthy controls. A panel of 15 cytokines representing Th1, Th2 and Th17 pathways was assayed using Multiplex Suspension Array platform. Plasma levels of five cytokines were found to be altered in GBS patients compared to healthy control subjects: (i) IL-1β exhibited reduced levels, and (ii) IFN-γ, IL-4, IL-21 and IL-33 were elevated in GBS patients. The most important finding of this study was up-regulated expression of IL-21 and IL-33 in patients with GBS. Given the role of IL-33 as an alarmin, the elevated level of this cytokine provides important indication about a much broader role of cytokines in GBS. This study also provides evidence towards a multi-lineage Th cells (Th1, Th2 and Th17) associated cytokine responses in the pathophysiology of GBS.